2020
DOI: 10.1155/2020/2158573
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Soil Organic Carbon Content Using Hyperspectral Remote Sensing in a Degraded Mountain Landscape in Lesotho

Abstract: Soil organic carbon constitutes an important indicator of soil fertility. The purpose of this study was to predict soil organic carbon content in the mountainous terrain of eastern Lesotho, southern Africa, which is an area of high endemic biodiversity as well as an area extensively used for small-scale agriculture. An integrated field and laboratory approach was undertaken, through measurements of reflectance spectra of soil using an Analytical Spectral Device (ASD) FieldSpec® 4 optical sensor. Soil spectra w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…The maximum value of RPD in the PLSR model was 1.68, with an average value of 1.55, which was less than the DOAR model. Therefore, it is concluded that based on the bow curvature, the DOAR model can predict the content of SOM, so that the accuracy of the DOAR model to predict the soil organic matter content was better than the PLSR model [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…The maximum value of RPD in the PLSR model was 1.68, with an average value of 1.55, which was less than the DOAR model. Therefore, it is concluded that based on the bow curvature, the DOAR model can predict the content of SOM, so that the accuracy of the DOAR model to predict the soil organic matter content was better than the PLSR model [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…A good performance model has a value for R 2 close to 1, with a lower RMSE and a higher RPD. RPD > 2.5 means that the model has excellent predictive ability, 2 < RPD < 2.5 means a good model, 1.5 < RPD < 2 means a relatively fair model, and RPD < 1.5 means that the model is incapable of prediction [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…In other studies, Kumar 22 applied CARS and PLSR to analyze toluene and pyrene mixtures based on excitation–emission matrix fluorescence spectroscopy. F. Bangelesa et al 23 utilized a portable spectrometer to capture the reflectance spectra of the soil and combined it with RFR to predict the soil organic carbon concentration.…”
Section: Introductionmentioning
confidence: 99%